Tetrandrine Prevents Bone Loss in Ovariectomized Mice by Inhibiting RANKL-Induced Osteoclastogenesis - Zhong, Zeyuan; Qian, Zhi; Zhang, Xu; Chen, Fancheng; Ni, Shuo; Kang, Zhanrong; Zhang, Fangxue; Li, Dejian; Yu, Baoqing (Frontiers in Pharmacology, 2020)
Postmenopausal osteoporosis (PMOP) is a metabolic bone disease characterized by decreased bone density and strength due to the imbalance between osteogenesis and osteoclastogenesis. Postmenopausal estrogen withdrawal increases proinflammatory cytokines and decreases the serum level of OPG, which then leads to the overactivation of osteoclastogenesis. Tetrandrine, a bis-benzylisoquinoline alkaloid, has been widely used in the treatment of rheumatoid arthritis clinically in China. Here we demonstrate that tetrandrine significantly prevented ovariectomy-induced bone loss and inhibited RANKL-induced osteoclastogenesis. In vivo, We found that intraperitoneal injection of tetrandrine (30 mg/kg) every other day markedly reduced bone loss in ovariectomized mice and the serum levels of TRAcp5b, TNF-a, andIL-6 were significantly decreased. In vitro, we found that tetrandrine significantly inhibited osteoclast differentiation in bone marrow monocytes and RAW264.7 cells according to the results of osteoclastogenesis‐related gene expression, tartrate-resistant acid phosphatase (TRAP) staining and actin-ring formation as well as bone resorption assay. Mechanistically, tetrandrine inhibited RANKL‐induced osteoclastogenesis by suppressing NF-kB, Ca2+and PI3K/AKT signaling pathways. Taken together, our findings suggest that tetrandrine suppresses osteoclastogenesis through modulation of multiple pathways and has potential value as a therapeutic agent for PMOP, especially for those suffering from RA and PMOP at the same time.